Current State of Distance Education Technologies: Analysis and Prospects in Higher Education - Olimova , Gulbahor (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article analyzes the current state of distance learning technologies in the higher education system, along with their pedagogical and technical characteristics. The research examines the advantages of distance learning, its impact on student performance, and trends at both global and national levels. Furthermore, the role of artificial intelligence and cloud technologies in enhancing the quality of education is highlighted.